Case Report: Aortic Regurgitation of Postocclusion and Long-Term Outcome Following PDA Correction in an Adult Dog - Ro, Woong-Bin; Park, Hee-Myung; Song, Doo-Won; Kim, Heyong-Seok; Lee, Ga-Won; Kang, Jin-Ho; Jo, Chan-Ho; Kang, Min-Hee (Frontiers in Veterinary Science, 2022)
A 9-year-old intact female Maltese dog was admitted for further evaluation of previously diagnosed patent ductus arteriosus (PDA). The dog showed severe coughing and exercise intolerance. On physical examination, a grade VI/VI continuous heart murmur was auscultated. Thoracic radiography demonstrated cardiomegaly, pulmonary overcirculation, and moderate bronchointerstitial pattern. Echocardiography revealed severe dilation of the left ventricle and atrium, decreased left ventricular contractility, and left-to-right PDA. On electrocardiography (ECG), R amplitude was increased. Computed tomographic angiography revealed type IIA PDA. The serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentration was >10,000 pmol/L. Transarterial occlusion was performed and the Amplatz® Canine Duct Occluder was successfully deployed. On echocardiography 48 h after the procedure, aortic regurgitation (AR) and residual ductal flow were noted. Long-term follow-up on clinical signs, physical examination, radiography, echocardiography, ECG, and serum NT-proBNP were evaluated until 30 months after correction of PDA. The clinical indices of physical examination, thoracic radiography, echocardiography, ECG, and serum NT-proBNP concentration were improved, although the postocclusion AR and residual ductal flow persisted. The dog followed up without clinical signs for 41 months following the correction. To our knowledge, this is the first case report to demonstrate quite a long time of follow-up (41 months) in an older dog with transarterial occlusion of PDA with postocclusion AR and residual flow.